Design and Implementation of a Dynamic and Informative Housing Consultant Website - Chandrawati, T. Brenda; Nugraha, Johanes Arya Pramesta; Rejeki, VG Sri; Anggita, Lintang Jata (SISFORMA, 2024)
With the advancement of the digital revolution, the way knowledge is accessed has evolved from traditional media to more flexible and interactive digital platforms. Early websites, which were primarily static and one-directional, struggle to keep up with user expectations for dynamic and frequently updated content. This research explores the design and development of scukrsjawa3.com, an interactive educational website aimed at providing structured and engaging learning resources. Utilizing the Rapid Application Development (RAD) approach, the website was built using PHP, JavaScript, CSS, and HTML, with Bootstrap ensuring responsiveness and ease of navigation. Key features include a well-structured content system, chatbot integration, and an intuitive user interface, enhancing accessibility and engagement. This platform meets the growing demand for interactive, real-time, and user-centric learning experiences, serving as an effective tool for digital education.